23. TỔNG QUAN HỆ THỐNG VỀ HIỆU QUẢ - AN TOÀN VÀ BẰNG CHỨNG KINH TẾ DƯỢC CỦA THUỐC RITUXIMAB TIÊM DƯỚI DA SO VỚI RITUXIMAB TIÊM TRUYỀN TĨNH MẠCH Ở NGƯỜI BỆNH U LYMPHO KHÔNG HODGKIN (Tạp chí Y học Cộng đồng, 2024)
Objective: This study synthesized evidence on the clinical and pharmacoeconomic aspects of subcutaneous (SC) versus intravenous (IV) rituximab for non-Hodgkin lymphoma (NHL).Methods: The systematic review was performed according to the PRISMA statement. The search was processed on PubMed, Scopus, and Embase until February 26, 2023. Studies reported the safety, efficacy, or cost-effectiveness of rituximab SC compared with rituximab IV among NHL patients were eligible for the analysis.Results: For evidence of efficacy and safety, three RCTs and one case-control study were included in the systematic review. The results showed no statistically significant difference between rituximab SC and rituximab IV in the safety or efficacy indicators for the treatment of NHL. In addition, results from eight pharmacoeconomic studies suggested that rituximab SC significantly helped shorten the time for healthcare workers as well as patients, and saved related costs compared to rituximab IV for the treatment of NHL.Conclusions: Rituximab SC and rituximab IV were proved to be not different in terms of safety and efficacy for the treatment of NHL. This review also indicated that compared to rituximab IV, rituximab SC saved time and costs for the treatment of NHL in a hospital setting.
Keywords: Rituximab; u lympho không Hodgkin; hiệu quả; an toàn; tổng quan hệ thống